2020
DOI: 10.1002/ijgo.13442
|View full text |Cite
|
Sign up to set email alerts
|

Male partner involvement and successful completion of the prevention of mother‐to‐child transmission continuum of care in Kenya

Abstract: Objective To examine the relationship between male partner involvement (MPI) in prevention of mother‐to‐child transmission (PMTCT) activities and successful completion of the PMTCT continuum of care, which remains sub‐optimal in settings with high prevalence of HIV. Methods A cross‐sectional survey was administered in June–August 2017 to a sample of 200 postpartum Kenyan women with HIV enrolled in a parent trial. Composite PMTCT and MPI variables were created. Descriptive, simple and multivariable regression, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Several studies reported that such factors were found to impact nevirapine uptake, ART treatment adherence, PMTCT continuum adherence, condom use, facility‐based childbirth, receive HIV test results, HIV self‐testing, postpartum HIV status, infant HIV acquisition through MTCT, MTCT knowledge and uptake of family planning. 16 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 (Supporting Information S1: Table 3 ) For example, women with partners who were involved in HIV testing, counseling or other PMTCT activities were more likely to: return for follow‐up to receive nevirapine 86 ; take maternal or infant dose of nevirapine 86 ; adhere to Option B plus ART treatment 87 ; successfully complete all steps in the PMTCT continuum 88 ; and, show improved retention in HIV care. 89 Postpartum women with a partner who ever refused the use of a condom were more likely to have a positive HIV status (Adjusted Odds Ratio = 1.88; 95% confidence interval 1.20, 2.90) compared to women with a partner who never refused.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies reported that such factors were found to impact nevirapine uptake, ART treatment adherence, PMTCT continuum adherence, condom use, facility‐based childbirth, receive HIV test results, HIV self‐testing, postpartum HIV status, infant HIV acquisition through MTCT, MTCT knowledge and uptake of family planning. 16 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 (Supporting Information S1: Table 3 ) For example, women with partners who were involved in HIV testing, counseling or other PMTCT activities were more likely to: return for follow‐up to receive nevirapine 86 ; take maternal or infant dose of nevirapine 86 ; adhere to Option B plus ART treatment 87 ; successfully complete all steps in the PMTCT continuum 88 ; and, show improved retention in HIV care. 89 Postpartum women with a partner who ever refused the use of a condom were more likely to have a positive HIV status (Adjusted Odds Ratio = 1.88; 95% confidence interval 1.20, 2.90) compared to women with a partner who never refused.…”
Section: Resultsmentioning
confidence: 99%
“…This is similar to our own findings with Rwandan couples [ 91 ]. Other studies have focused on couples with one or both partners HIV+ [ [92] , [93] , [94] , [95] , [96] ] and have examined patterns of communication in couples and enhanced male involvement in HIV prevention with pregnant women [ [97] , [98] , [99] , [100] ], though without a specific focus on negotiated agreements [ 51 , [101] , [102] , [103] , [104] ].…”
Section: Discussionmentioning
confidence: 99%
“…A total of 183 HPs were enrolled in the study, with the median age of 37 years (IQR, [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44]. Less than a quarter (19%) were male.…”
Section: Pmtct Knowledge and Practices Of Health Providers Descriptio...mentioning
confidence: 99%
“…testing of male partners of pregnant women is a relevant strategy to increase the use of PTMCT services [38][39][40].…”
mentioning
confidence: 99%